2000
DOI: 10.1017/s0016756800004520
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-group mineralization in the Tertiary Igneous Province: new data from Mull and Skye, Scottish Inner Hebrides, UK

Abstract: In recent years, platinum-group mineral deposits have been reported from several of the Tertiary igneous complexes in East Greenland. These intrusions form part of the same igneous province as the Tertiary igneous centres in northwest Scotland, and recent work confirmed the presence of abundant platinum-group minerals in the Rum Central Complex. In this paper we report for the first time the presence of abundant and diverse platinum-group minerals from the Tertiary Ben Buie intrusion on Mull and the Cuillin Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Type-2 BMS and PGM crystallized from this fluid phase and are thus locally intimately associated with ferrian chromite. A very similar process was proposed by Coghill & Wilson (1993) for the Great Dyke (but they invoked "microscale" remobilization of PGM, not observed in the Baula Complex), and by Pirrie et al (2000), where a combined orthomagmatic-hydromagmatic origin is proposed for the Mull Complex in Scotland.…”
Section: Synthesissupporting
confidence: 56%
“…Type-2 BMS and PGM crystallized from this fluid phase and are thus locally intimately associated with ferrian chromite. A very similar process was proposed by Coghill & Wilson (1993) for the Great Dyke (but they invoked "microscale" remobilization of PGM, not observed in the Baula Complex), and by Pirrie et al (2000), where a combined orthomagmatic-hydromagmatic origin is proposed for the Mull Complex in Scotland.…”
Section: Synthesissupporting
confidence: 56%
“…However, it is worth noting that Day et al (2008) reported Os concentrations of > 200 ppb in unit 22 chromitite (an order of magnitude greater than that reported by Barnes and Francis, 1995), suggesting that there may be a degree of intra-reef variability too. Other detailed PGM studies, such as those carried out by Pirrie et al (2000) on chromitites in the ∼ 60 Ma Mull and Skye layered intrusions (British Paleogene Igneous Province) support the general point however, that LMIhosted (stratiform) chromitite seams tend to be enriched in PGM. Furthermore, Halkoaho et al (1990) describe the Sompujärvi PGE Reef at the boundary between the third and fourth megacyclic unit in the Penikat layered intrusion (Finland), noting that where associated with disseminated chromite, the PGE grade is distinctly higher.…”
Section: Petrogenesis Of the Merensky Reef And The Ug2 Chromitite: 'Umentioning
confidence: 86%
“…On Skye, the Cu and Ni Laurite, irarsite, braggite, kotulskite, 1999;Power et al 2000a) s u l phides michenerite, moncheite, electrum, hongshiite, etc. Ben Buie, Mull (Pirrie et al 2000) Chromitite (sulphide-poor) Laurite, irarsite, sperrylite, Pd-Bi-Sb, Pd-Bi-Te, etc. Peridotite Series, Skye (Pirrie et al 2000) Chromitite (largely sulphide-poor) Laurite, sperrylite, ruarsite, Pd-Bi-Te, etc.…”
Section: Geological Settingmentioning
confidence: 99%
“…Ben Buie, Mull (Pirrie et al 2000) Chromitite (sulphide-poor) Laurite, irarsite, sperrylite, Pd-Bi-Sb, Pd-Bi-Te, etc. Peridotite Series, Skye (Pirrie et al 2000) Chromitite (largely sulphide-poor) Laurite, sperrylite, ruarsite, Pd-Bi-Te, etc. Greenland Skaergaard (Bird et al 1991; First appearance of disseminated Cu (Cu,Fe)(Pd,Au,Pt) alloys, electrum, atokite, et al 1998) sulphides zvyagintsevite, hongshiite, kotulskite, etc.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation